PENGARUH KEPEMIMPINAN TRANSAKSIONAL TERHADAP MOTIVASI KERJA KARYAWAN Pada Kantor PT. Wijaya Sukses Sejahtera di Kabupaten Berau - Taruk Todingallo Delvi Awan (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
This study aims to determine the effect of transactional leadership on employee work motivation at PT. Wijaya Sukses Sejahtera in Berau Regency. The variables used in this study consisted of independent variables, namely contingent reward (X1), exception management (X2), and exploitative management (X3) and the dependent variable was work motivation (Y). Simultaneous test (F test) with 95% confidence level of employees in the office of PT. Wijaya Sukses Sejahtera in Berau District proves that simultaneously Contingent Reward variables (X1), active exception management (X2), and passive exception management (X3) amounted to 11.541 so (11.541> 2.76) significantly influence work motivation (Y). The results of the t-test are known that the contingent reward indicator is the most influential indicator on the performance of employees at PT. Wijaya Sukses Prosperous Berau. Thus proving the hypothesis influential on work motivation simultaneously received (H0 is rejected and Ha accepted).